Wood Carving Based on Computer Numerical Control (CNC) - Mohamed Yusof, Anizam; Mohd Bakri, Ummi Najwa; Ab. Rahman, Azmanirah (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: The development of wood carving machines based on computer numerical controls (CNC) is an innovation that researchers are translating into today’s technology world. This carving machine was developed because wood carpenters in the Small Medium Industries (SMEs) are still using manual carving methods with the use of hand tools. This manual carving method has raised several issues including shortage of skilled labour, low productivity, and lack of capital to own a wood carving machine. Therefore, the development of wood carving machines based on the computer’s numerical controls can assist entrepreneurs in solving any problems arising in the process of manual wood carving. The researcher has used the Engineering Design Process (EDP) development model as the main reference that involves the process of analysis, design, development, implementation, testing and evaluation in developing this machine. The testing consists of a carving time test, carving accuracy test, carving depth test and electrical test on the control circuit. Thus, the objectives of the development have been achieved. Keywords: Wood Carving, Computer Numerical Control (CNC)